The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/jmse4010007
|View full text |Cite
|
Sign up to set email alerts
|

Biobanking of a Marine Invertebrate Model Organism: The Sea Urchin

Abstract: The sea urchin has long been used as an invertebrate model organism in developmental biology, membrane transport and sperm oocyte interactions, and for the assessment of marine pollution. This review explores the effects of cryopreservation and biobanking in the biology and development of sea urchins, all the way from germaplasm through to juveniles. This review will provide an integral view of the process and all that is known so far about the biology of cryopreserved sea urchins, as well as provide an insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 59 publications
2
26
0
Order By: Relevance
“…In this study, the high total sperm motility after thawing was obtained at 5%–20% DMSO, as well as fertilization rate. The results reported in this investigation was consistent with other studies that concentrations from 5% to 10% were found suitable for oyster, pearl oyster and sea urchin specimens (Hassan et al, ; Liu et al, ; Paredes, ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the high total sperm motility after thawing was obtained at 5%–20% DMSO, as well as fertilization rate. The results reported in this investigation was consistent with other studies that concentrations from 5% to 10% were found suitable for oyster, pearl oyster and sea urchin specimens (Hassan et al, ; Liu et al, ; Paredes, ).…”
Section: Discussionsupporting
confidence: 93%
“…lividus is considered a keystone herbivore, able to transform communities dominated by macroalgae into barren areas thereby reducing biodiversity and altering ecosystem functions [ 35 , 36 ]. The sea urchin has been extensively used as an invertebrate model organism in developmental biology and in ecotoxicology studies to assess the effects of marine pollution on marine organisms [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Echinoids have been considered ideal models for monitoring marine environmental hazards [ 11 ], because they are often key herbivore species, having a major role in structuring and controlling macroalgal assemblages, thereby shaping the benthic seascape, and also playing an important role in coastal food webs throughout the world [ 12 16 ]. They have traditionally been used as model organisms to study reproduction and early cell differentiation, sperm-oocyte interactions and apoptosis [ 17 19 ]. These organisms have been also proposed as valuable bioindicators for detecting environmental perturbations [ 20 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a cryopreservation protocol described for P. lividus sperm (Fabbrocini et al, 2014) that yields good motility. Cryopreservation protocols already exist or are under development for different developmental stages for 10-14 different sea urchin species (embryos and sperm), and since sea urchins are a highly demanded model, more applications will probably be further developed soon using cryopreserved cells, including toxicology (Paredes, 2015a).…”
Section: Cryopreserved Echinoidsmentioning
confidence: 99%